Visual Management of Time - Daniel L. Golden (In the Beginning was the Image: The Omnipresence of Pictures, 2016)
There is a striking contradiction betweentimeas one of the most fundamental constituents of human existence, and as one of our most abstract concepts ever. While – as we can learn from inquiries made by Kristóf Nyíri (2006, 2007, 2016) – the sense of time is deeply embedded in our bodily subsistence from heartbeats to motoric gestures, this kinesthetic-biological background cannot give an exhaustive account of time functioning as a social institution. The importance of the latter was realized by several theoreticians of modern society from the early 20th century. According to Georg Simmel (1903), metropolitan life presupposes the precise coordination